ANTESEDEN LUAS LINGKUP PENGUNGKAPAN SUKARELA DAN PENGARUHNYA TERHADAP ASIMETRI INFORMASI - sawitri, aristha purwanthari (Majalah Ekonomi, 2016)
This study aimed to find out the effect of firm characteristics (firm size, public share and the age of the company), reputation public accountant, leverage and firm performance (liquidity and profitability) to voluntary disclosure and to examine voluntary effect disclosure to asymmetry information. This research uses 108 manufacturing companies. The analysis method of the data uses multivariate regression. The result of this research shows that : 1) the age of the company, reputation public accountant, leverage, liquidity, profitability do not indicate certain significance influence towards the level of disclosure of financial statement completeness 2) the age of the company and public share significantly influence towards the level of disclosure of financial statement completeness 3) the level of disclosure of financial statement completeness does not indicate certain significance influence towards the asymmetry information Keywords: voluntary disclosure, firm characteristics, reputation public accounting, leverage and asymmetry information